2019
DOI: 10.1108/s1057-629020190000019009
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Discrimination on Immigrant and Refugee Physical and Mental Health

Abstract: Purpose Discrimination has been identified as a major stressor and influence on immigrant health. This study examined the role of perceived discrimination in relation to other factors, in particular, acculturation, in physical and mental health of immigrants and refugees. Methodology/approach Data for US adults (18+ years) were derived from the National Epidemiologic Survey on Alcohol and Related Conditions. Mental and physical health was assessed with SF-12. Acculturation and perceived discrimination were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 89 publications
(140 reference statements)
6
68
2
Order By: Relevance
“…Nurse researchers engaged in CBPR have a particular challenge in winning and maintaining trust in immigrant communities, given the strong anti‐immigrant sentiment that has become pervasive in various cities and towns across the globe. Data from a variety of studies suggest that erosion of trust in the health care system, due to discrimination and fears of detention and deportation, is resulting in adverse health outcomes among immigrants (D’Alonzo et al., 2020; Novak, Geronimus, & Martinez‐Cardoso, 2017; Szaflarski & Bauldry, 2019; Torres et al., 2018). In addition, immigrants are more likely to report instances of health care discrimination (Hacker, Anies, Folb, & Zallman, 2015; Rivenbark & Ichou, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse researchers engaged in CBPR have a particular challenge in winning and maintaining trust in immigrant communities, given the strong anti‐immigrant sentiment that has become pervasive in various cities and towns across the globe. Data from a variety of studies suggest that erosion of trust in the health care system, due to discrimination and fears of detention and deportation, is resulting in adverse health outcomes among immigrants (D’Alonzo et al., 2020; Novak, Geronimus, & Martinez‐Cardoso, 2017; Szaflarski & Bauldry, 2019; Torres et al., 2018). In addition, immigrants are more likely to report instances of health care discrimination (Hacker, Anies, Folb, & Zallman, 2015; Rivenbark & Ichou, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants may also face stressors related to discrimination or marginalization. The detrimental relationship between perceived discrimination and mental health has been documented among immigrants (17) and various racial/ethnic minority groups (18). Experiences or perceptions of discrimination may vary based on many factors, including education, age, race, heritage, length of time living in the United States, level of assimilation to the host culture, and characteristics of the area of settlement (19)(20)(21)(22)(23).…”
Section: Vulnerability To Mental Disorders Among Us Immigrantsmentioning
confidence: 99%
“…Prejudice and discrimination related to immigrants are also a critical problem [25,26]. A survey conducted by the Ministry of Justice of Japan reported that 30 percent of foreign nationals experienced discrimination, 40 percent were declined residence, and 25 percent were not employed because of their nationality [27].…”
Section: Introductionmentioning
confidence: 99%